2011
DOI: 10.1021/bm200679w
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Release of Lysozyme from Gelatin Microspheres: Effect of Cross-linking Agents and Thermoreversible Gel as Suspending Medium

Abstract: This study was aimed to characterize the microstructure and the performance of gelatin microspheres (GMs) cross-linked by two different cross-linkers viz. d-glucose and glutaraldehyde. New formulations were obtained, suspending the GMs in a thermoreversible Pluronic F127 (PF127) liquid-crystalline gel. Lysozyme was used as a model biomacromolecular drug to evaluate release features. Both types of cross-linked GMs were prepared by thermal gelation method. The lysozyme-loaded microspheres were characterized by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In another study, Hiwale and co-workers studied combined formulation of gelatin microspheres and thermoreversible gel as a drug-depot system for lysozyme [161]. Gelatin microspheres (GMs) loaded with lysozyme were prepared using two different cross linking agents: d -glucose and glutaraldehyde.…”
Section: Colloidal Delivery Systemsmentioning
confidence: 99%
“…In another study, Hiwale and co-workers studied combined formulation of gelatin microspheres and thermoreversible gel as a drug-depot system for lysozyme [161]. Gelatin microspheres (GMs) loaded with lysozyme were prepared using two different cross linking agents: d -glucose and glutaraldehyde.…”
Section: Colloidal Delivery Systemsmentioning
confidence: 99%
“…[1][2][3][4] Being categorized as a safe excipient by the US Food and Drug Administration (FDA), gelatine has shown great promise as a component of biomaterials in many medical applications. 5,6 For example, gelatine nanoparticles have been successfully utilized for non-viral plasmid DNA delivery 7 and cationic gelatine plasmid DNA polyplexes, i.e.…”
Section: Gelatinementioning
confidence: 99%
“…Many approaches have been adopted to modulate drug release kinetics, among which a combination of different delivery systems is a simple one. For example, to decrease burst release, microspheres in combination with in situ gels have been reported in some studies; [19][20][21] however, few, if any, studies have reported on PEGylation in combination with ISFS. PEG is the most successful candidate …”
Section: In Vivo Studiesmentioning
confidence: 99%